Faculty of journalism: traditions, personalities, innovations. 80th anniversary of the faculty of journalism of Belarusian State University - Vorobiev, Vasily P. (Journal of the Belarusian State University. Journalism, 2024)
The article is dedicated to the 80th anniversary of the faculty of journalism of Belarusian State University. The process of formation of educational and research traditions of the team, the role of the teacher’s personality in the life of the educational centre, and the innovative potential of journalistic higher education are outlined.
Keywords: faculty of journalism; traditions; personalities; innovative potential